2006
DOI: 10.1016/j.yhbeh.2005.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal state influences aspects of female mate choice in the Túngara Frog (Physalaemus pustulosus)

Abstract: Females alter their mate choices as they transition through different reproductive stages; however, the proximal mechanisms for such behavioral fluctuation are unclear. In many taxa, as females transition through different reproductive stages, there is an associated change in hormone levels; therefore, we examined whether fluctuation in hormone levels serves as a proximal mechanism for within-individual variation in mate choice in female túngara frogs (Physalaemus pustulosus). We manipulated hormone levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 60 publications
5
76
1
Order By: Relevance
“…In the túngara frog, a previous study showed that hCG, which stimulates production of gonadal steroids (Lynch et al, 2006;Wu et al, 2001), increases egr-1 expression in the laminar nucleus of the torus (Lynch and Wilczynski, 2008). Our findings suggest that the effect observed by Lynch and Wilczynski (2008) was mediated by estradiol and not by direct effects of gonadotropins (Yang et al, 2007) or through changes in other steroids, such as progesterone or androgens.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In the túngara frog, a previous study showed that hCG, which stimulates production of gonadal steroids (Lynch et al, 2006;Wu et al, 2001), increases egr-1 expression in the laminar nucleus of the torus (Lynch and Wilczynski, 2008). Our findings suggest that the effect observed by Lynch and Wilczynski (2008) was mediated by estradiol and not by direct effects of gonadotropins (Yang et al, 2007) or through changes in other steroids, such as progesterone or androgens.…”
Section: Discussionsupporting
confidence: 50%
“…Furthermore, in the auditory midbrain and parts of the limbic forebrain, estradiol receptor expression is sexually dimorphic , suggesting that estradiol is an important modulator of neural circuits underlying female-typical behavior. In addition, injections of human chorionic gonadotropins (hCGs), which stimulate production of gonadal steroids (Lynch et al, 2006;Wu et al, 2001), increase neural responses to conspecific social signals in the auditory midbrain (i.e. torus semicircularis) (Lynch and Wilczynski, 2008), suggesting that one way that estradiol modulates behavioral responses to conspecific calls is through modulation of auditory responses (Lynch and Wilczynski, 2008) or through integration of auditory and motor systems (see Hoke and Pitts, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study on plasticity in mating preference in Túngara frog females (Lynch et al, 2005) has shown that the probability of recognizing both a conspecific call (receptivity) and a call less attractive than a conspecific call (permissiveness) changes during the reproductive stages of females, probably because of differences in their hormonal state (Lynch et al, 2006). Receptivity and permissiveness are higher in the amplexed than in the pre-and post-amplexed stages, but the probability of discriminating between two conspecific calls of different attractiveness does not change.…”
Section: The Perceived Utility Of Prospective Mates: U = P(a|h)/p(a|hmentioning
confidence: 99%
“…Socially induced plasticity, as with seasonal and hormonally induced plasticity, should facilitate detection and/or recognition of the conspecific vocal signals that are crucial for guiding reproduction. It is not yet clear whether these effects are mediated by socially induced hormone changes (Burmeister and Wilczynski, 2000;Lynch et al, 2006) or occur independently. Nevertheless, our data add to the evidence that the social stimulation that occurs during a breeding season is an important factor in shaping the responses of the peripheral auditory system.…”
Section: Forward Masking and Socially Induced Plasticitymentioning
confidence: 99%